Sistem Pemantauan Saturasi Oksigen dan Detak Jantung pada Anak Menggunakan NodeMCU Dan Sensor MAX30100 - Ahmad Zulfikar Tanjung; R Tommy Gumelar; Shevti Arbekti Arman (Jurnal Teknologi Informasi (JUTECH), 2026)
Internet of Things (IoT) based health monitoring systems have become an increasingly important solution in individual health monitoring efforts. In this study, we designed and implemented a system for measuring oxygen saturation (SpO2) and heart measurement in children using the MAX30100 sensor and the NodeMCU ESP8266 microcontroller. This research aims to provide an effective solution in real-time monitoring of children's health. The MAX30100 sensor is used to accurately measure SpO2 and measure the heart through photoplethismogram (PPG) technology. Data obtained from sensors is processed by the NodeMCU ESP8266 microcontroller and sent in real-time via the Internet network to the Firebase Realtime Database. The data is then displayed on a website that can be accessed online, allowing users to easily monitor the child's health condition. The test method is carried out by measuring the results of SpO2 measurements and heart measurements with conventional medical devices as a comparison. The test results show that the designed system is capable of producing data that is accurate and in accordance with conventional medical devices. In this study, a security mechanism was also implemented for sending and storing data through the Firebase service, which provides an adequate level of security for health data. With this design and implementation, it is hoped that this system can provide real benefits in real-time monitoring of children's health.